2009
DOI: 10.1111/j.1748-0361.2009.00233.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Comfort Level With Emergency Interventions in the Rural Hospital Setting

Abstract: Number and type(s) of certifications and years of experience as an RN were associated with higher comfort levels. Responses to open-ended questions provided insight into the realities of rural emergency nursing and strategies for improving comfort levels of rural nurses in emergency situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…On occasion, they cared for acutely unwell patients for many hours before physician review. While Nurse practitioners and advanced care nurses play a key role in independent management of both minor and critical illness, there is little evidence that the departments in our review, or small rural hospitals in general, support such training.…”
Section: Discussionmentioning
confidence: 86%
“…On occasion, they cared for acutely unwell patients for many hours before physician review. While Nurse practitioners and advanced care nurses play a key role in independent management of both minor and critical illness, there is little evidence that the departments in our review, or small rural hospitals in general, support such training.…”
Section: Discussionmentioning
confidence: 86%
“…The impact of the contagiousness of the disease besides the change in the nurses' working environment during the pandemic period was found to affect the nurses' comfort levels 37 . Ross and Bell (2009) reported that the comfort level of nurses is moderate in emergency interventions such as thoracentesis and precipitous vaginal delivery. In Maiorini's study, the total comfort level score indicated that nurses were very comfortable managing in acute infusion reactions from antineoplastic agents 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the critical event itself may affect how medical teams respond to each specific circumstance. Thus, algorithms of medical care that are adaptive to the unique infrastructure that characterizes CAHs may help to standardize and thus improve clinical practice (Ross & Bell, ).…”
Section: Discussionmentioning
confidence: 99%